Cassava Productivity Growth in Nigeria (2019)
Cassava has gained prominence in the world and has become economic crop in the Nigerian agricultural sector. Secondary data was used for this study. The required variables were extracted from General Household Survey Panel Data (GHS-P). The GHS-P is a nationally representative survey of households across Nigeria covering urban and rural sectors. Analytical tools used included Total factor productivity and Markov chain. 82% of populations of Cassava farmers are in the rural areas and close to 73% were young adults including both male and female involved in cassava production. Approximately 65% of the cassava based farmers were single that not yet married and most of the farmers were educated and about 80% and 98% of the cassava based farmers did not have access to credit facilities and extension personnel respectively. Generally, the cassava productivity growth was erratic and very small proportion of cassava farmers that were in lower productivity reduced overtime, while the minimal proportion of cassava farmers that moved into both moderate and high productivity increased overtime respectively. Generally, there is more to be done to increase and attain sustainable high level cassava productivity growth in Nigeria.